FEASIBILITY STUDY OF POWER SAVING BASED ON USING EMMEDUE M2 BUILDING SYSTEM (Journal of Engineering, 2008)
The present work concentrates on the feasibility of the heat load reduction by utilizing some structural material with very poor heat conductivity as isolators for heat transmission. Average annular heating and cooling load is estimated for a typical building of certain area and design using ordinary structural material and EMMEDUE M2 building system. The basic element of the new structural material is made of a foam polystyrene core that is self extinguishing and chemically inert with varying density and thickness depending on panel type. The calculations are based on the average maximum and minimum monthly temperature in Baghdad. Building heating load could mainly depend on the average temperature difference per each daily hour per year, while building cooling load components are; direct solar radiation, transmission load, ventilation/infiltration load and internal load. Except the transmission load which depends on the same average temperature difference the other factors could be calculated separately.A reduction of 55% in the annual load is estimated per each house using the new building technology. For a district sums up 1000 houses of the new structural design the total saving of power will be 10.45 MW. The saving in heating and cooling cost is estimated based on capital cost of the diesel generation system and the fuel consumption cost. It has been concluded that the passive structural heat isolation is a very effective manner in countries like Iraq which has severe temperature differences between thesummer and winter seasons.